Advances of Non-iron Metal Nanoparticles in Biomedicine - Anroop B. Nair; Mohamed A. Morsy; Pottathil Shinu; Sabna Kotta; Mithra Chandrasekaran; Abu Tahir (Frontiers Media S.A., 2021)
Metal nanoparticles (MNPs) comprise of nanoparticles originating from metallic elements with additional properties inherent to metal ions. MNPs found applications in various field such as electronics, optics, mechanics, physics etc. There are many reviews on iron MNPs for biomedical application. Hence, in this review, we focus on non-iron MNPs and their vivid biomedical applications. Here, we review the applications of non-iron MNPs in biomedicine such as drug delivery, gene delivery, anticancer activity, antimicrobial activity, tissue engineering, bioimaging, and photodynamic, and photothermal therapies.